Loneliness, Labor, and Longing: A Contemporary Thematic Analysis of Steinbeck’s of Mice and Men - MUHAMMAD ILHAM ALI (Jurnal Vokasia, 2026)
This study employs an analytic review approach to examine the thematic construction in John Steinbeck’s Of Mice and Men, focusing on its portrayal of companionship, loneliness, and the fragility of dreams. These themes are explored as narrative mechanisms that reflect the social and psychological realities of marginalized individuals during the Great Depression. The analysis investigates how Steinbeck's depiction of human relationships and aspirations serves as a lens for understanding broader issues of alienation, economic disenfranchisement, and emotional resilience. Utilizing recent theoretical frameworks from literary and cultural studies, the study systematically interprets character interactions, plot developments, and symbolic elements to uncover the deeper meanings embedded in the text. Through qualitative thematic analysis, the novella is shown to articulate a complex emotional landscape in which hope and despair coexist. The bond between George and Lennie emerges as a counterpoint to the dominant atmosphere of isolation, while the recurring motif of unattainable dreams underscores the characters’ internal and external struggles. Findings suggest that Steinbeck’s work maintains enduring relevance by offering insight into universal human experiences such as connection, sacrifice, and the pursuit of meaning under systemic pressures. The study concludes that Of Mice and Men is not only a historical narrative but also a profound commentary on the human condition, demonstrating literature’s capacity to foster empathy and critical reflection across generations.